Physical and Engineering Properties of Dry, Soaked and Pregerminated Paddy Seed (Basmati-370) - Chaudhary, Divakar; Sharma, Sushil; Sharma, Manish Kumar; Bhardwaj, Sushant (Emerging Issues in Agricultural Sciences Vol. 1, 2023)
Designing and developing the size and shape of the drum's orifice in a drum seeder depends heavily on the physical and engineering characteristics of paddy seeds. In order to determine these dimensions, the physical and engineering characteristics of dry, soaked (12-hour soaking), and pregerminated (24-hour soaking + 12-hour incubation) paddy (Basmati-370) seeds were investigated. The mean value for; length, width, thickness and equivalent diameter (mm) varies from 9.95 to 10.55, 10.98 to 11.61, 12.01 to 12.53 mm; 1.95 to 2.12, 2.41 to 2.57, 2.67 to 2.90 mm; 1.70 to 1.74, 2.06 to 2.18, 2.29 to 2.48 mm; and 3.07 to 3.20, 3.55 to 3.68, 3.81 to 4.11 mm for dry, soaked and pre germinated seeds respectively. The aspect ratio and sphericity were found to be 0.19, 0.24, 0.28 and 30, 32.88 and 34.70% for dry, soaked and pregerminated seeds respectively. The volume, aspect ratio, and terminal velocity of soaked seed and pre germinated seed increased by 21, 26.31, and 15.31%, and 39.98, 47.36, and 18.91%, respectively, when compared to dry seed.